(untitled) (International Journal of Engineering and Computer Science, 2017)
Green chemistry aims to provide environmentally benign products from sustainable resources, using processes that do not harm people or the environment. Most chemical reactions have been correlated in molecular solvents. Recently , have even, a new clan of solvents has emerged “ Ionic Liquids “.“. Ionic liquids (ILs) are new organic salts that exist as liquids at low temperature (<100oC). An important future of ILs is immeasurably low vapor pressure. For this reason they are called green solvents in contrast to traditional Volatile Organic Solvents (VOCs). ILs have many attractive properties such as chemical and thermal stability , inflammability , high ionic conductivity and a wide electrochemical potential window . Therefore they have been extensively investigated as solvents or cocatalyst in various reactions including organic catalysis and inorganic synthesis, Bio-catalysis and polymerization. Ionic liquids find application in alkylations, allylations, hydroformylations, epoxidations, synthesis of ethers, Friedel craft reaction, Diel-Alder Reaction, Knoevengal condensation and Wittig reaction. ILs have been claimed as being „„green solvents‟‟ and possible alternative to volatile organic solvents. This has been justified in some applications where ILs, because of their negligible vapour pressure and non-flammability, are used favourably instead of chlorinated solvents. An example is given by the development of an optimised process for degreasing and/or scouring metal, ceramic, glass, plastic composite material or semiconductor surface, by treatment of the surfaces in a solution comprising an IL .Some ILs have been the subject of toxicity and ecotoxicity studies and data are now available on a larger variety of organisms (bacteria, fungi, fish , algae.). Most studies have been carried out on imidazolium- and pyridinium-based ILs, with alkyl or alkoxy side chains. The variety of anions studied is limited mainly to bromide, chloride, hexafluorophosphate and tetrafluoroborate. Much less research has been devoted to the determination of the biodegrade-ability of ILs but the design of biodegradable ILs has been covered in recent papers. A high throughput screen based on the Agar Diffusion method was recently applied to test, in a first rapid approach, the toxicity of ILs towards microorganisms and to distinguish toxic and biocompatible ILs. My case study is about to produce effective yield of product from the reactants by choosing selective Ionic Liquids through Green mechanism. Now in modern area of ILs stems from the work on “Alkyl pyridinium “and “Dialkyl imidazolium” salts are used as green solvents.>